The Effect Wilting Tangerine Peel on Characteristics of Powder Used In Food Self-Heater - Rini Rini; Daimon Syukri; Puja Nadia Sukma (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
A food self-heater is a device designed to rapidly heat food by the utilization of exothermic or endothermic reactions. To yet, a food self-heater with a dedicated scent feature has not been developed. The fragrance utilized is derived from residual tangerine peel components. The objective of this study is to investigate the variations in the concentration of the limonene compound in essential oil extracted from tangerine peel, specifically examining the impact of tangerine peel wilting. Additionally, the study intends to identify the most effective food self-heating method by incorporating tangerine peel powder as an aromatic component in the self-heating process. The present study employed a Completely Randomized Design (CRD) consisting of five treatments and three replications. The treatments employed in this study encompassed varying durations of withering time for tangerine peel, denoted as A (0 hours), B (6 hours), C (12 hours), D (24 hours), and E (48 hours). The research findings indicated that the duration of drying tangerine peels had a notable impact on various factors including water content, yield, pH, color, duration for the aromatic self-heating meal to attain the optimal temperature, and aroma. However, no significant influence on limonene levels was seen. Based on the duration required for the aromatic food self-heater to attain the optimal temperature and the organoleptic aroma, treatment D (24-hour withering of tangerine peel) demonstrates the highest efficacy. This treatment exhibits a time frame of approximately 4.5 minutes for the aromatic food self-heater to reach the optimum temperature, accompanied by a fragrance rating of 4.2 in the organoleptic analysis.